Should non-citizens have access to publicly funded health care?. Issue 9 (September 2015) - Sun, L.-Y.; Lee, E.-W.; Zahra, A.; Park, J.-H.
Abstract Objectives To analyse public attitudes towards access for non-citizens to publicly funded health care and to assess the factors that affect such attitudes. Study design Cross-sectional study. Methods Data from 29 countries were used for a multilevel regression, and data from four countries (United States, Sweden, Philippines, and Korea) were used for a linear regression. The data were collected from the International Social Survey Program (ISSP), the World Bank, the Organization for Economic Cooperation and Development (OECD), and the United Nations. The dependent variable was considered to be agreement for non-citizen access to publicly funded health care. The independent variables included: the gross national income (GNI), the gross national income coefficient (GINI), sex, age, education, household income, employment, health insurance, self-related health status, chronic illness, percent having insurance, percent having public insurance, percent employed, percent migrants, percent of health expenditure of the total gross domestic product (GDP), and percent of social expenditure of the total GDP. Egalitarianism for education policy (EEP), egalitarianism for health policy (EHP), and willingness to contribute to an egalitarian health policy (WCHP) were also examined. Results In the countries surveyed, more than half of the citizens agreed that non-citizens should have access to publicly funded health care. Agreement with that statement had a negative trend with respect to the GNI. The percent having public insurance and WCHP had a significantly positive association with agreement while the percent of those with insurance had a negative relationship. In the USA, household income, EHP, and WCHP were positively associated with agreement, while females were inversely associated with agreement. In Sweden, having health insurance had an inverse association to agreement while females, postsecondary education, health insurance coverage, and WCHP were positively associated with agreement. In the Philippines, household income, EEP, and EHP had significant negative associations with agreement while WCHP had a positive relationship. In Korea, household income and self-rated health status were positively associated with agreement, while postsecondary education had a negative association. Conclusion Public attitudes towards allowing non-citizens to have access to publicly funded health care present high levels of variation, even among developed countries or countries with similar GDPs. The specific socio-economic conditions within a country and an individual's own social, demographic, and economic background can have different effects on the individual's attitudes towards non-citizens. On a global level, coverage of public health insurance plays an important role for enhancing the public's positive attitudes towards non-citizens' access to publicly funded health care. On a national level, health care policies tailored toward non-citizens based on the specific situation of each country and region are necessary.